Minoan Realities - Diamantis Panagiotopoulos, Ute Günkel-Maschek (dir.). (Aegis Actes de colloques, 2012)
What is the social role of images and architecture in a pre-modern society? How were they used to create adequate environments for specific profane and ritual activities? In which ways did they interact with each other? These and other crucial issues on the social significance of imagery and built structures in Neopalatial Crete were the subject of a workshop which took place on November 16th, 2009 at the University of Heidelberg. The papers presented in the workshop are collected in the pres